Effect of chitosan from shrimp shells (Litopenaeus vanname) as an irigation solution on root canal dentine microhardness: Pengaruh kitosan dari cangkang udang Litopenaeus vanname terhadap kekerasan mikro dentin saluran akar - Mattulada, Indrya Kirana; Asmah, Nur; Syam, Syamsiah; Abdi, Muhammad Jayadi; Nurfitriana, Besse (Makassar Dental Journal PDGI Makassar, 2024)
The most commonly used irrigation agent today is ethylene diamine tetra-acetic acid (EDTA) 17%; to remove the inorganic com-ponents of the smear layer in the root canal. However, EDTA can cause demineralisation of dentin in the root canal wall. Shrimp shells (Litopenaeus vannamei) contain calcium, protein and chitin. Chitin can be utilised in the manufacture of chitosan which is non-toxic, biocompatible, biodegradable, antimicrobial. This article shows the effect of chitosan from shrimp shells as an irrigati-on solution on the microhardness of root canal dentin. Laboratory experimental study with pretest posttest with control group de-sign using mandibular premolar teeth divided into 3 groups, each consisting of 9 teeth. Group 1 was irrigated with aquadest, group 2 with 0.2% chitosan and group 3 with 17% EDTA. The samples were tested using a Vicker hardness tester. Data were ana-lysed using paired t-test and one-way Anova. The data obtained in the irrigation of distilled water solution did not decrease the microhardness of root canal dentin, while the chitosan solution irrigation treatment experienced a lower than EDTA 17% (p<0.05). It was concluded that irrigation with 0.2% chitosan solution decreased the microhardness of root canal dentin which was lower than 17% EDTA solution.